2021
DOI: 10.3390/biom11111608
|View full text |Cite
|
Sign up to set email alerts
|

Under Conditions of Amyloid Formation Bovine Carbonic Anhydrase B Undergoes Fragmentation by Acid Hydrolysis

Abstract: The development of many severe human diseases is associated with the formation of amyloid fibrils. Most of the available information on the process of amyloid formation has been obtained from studies of small proteins and peptides, wherein the features of complex proteins’ aggregation remain insufficiently investigated. Our work aimed to research the amyloid aggregation of a large model protein, bovine carbonic anhydrase B (BCAB). It has previously been demonstrated that, when exposed to an acidic pH and eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Recently, more detailed description of morphological types of these fibrils has been published [ 25 ]. It was shown that a distinctive feature of the I208A fibrils is their specific morphology characterized by the lateral protofilaments association and formation of fibril ribbons, while the other mutant variants form worm-like, twisted, or single-long fibrils.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, more detailed description of morphological types of these fibrils has been published [ 25 ]. It was shown that a distinctive feature of the I208A fibrils is their specific morphology characterized by the lateral protofilaments association and formation of fibril ribbons, while the other mutant variants form worm-like, twisted, or single-long fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the observed amyloids are formed not of full-size proteins but of fragments of polypeptide chain derived via hydrolysis of the proteins. The detailed study of this mechanism of amyloid formation of carbonic anhydrase II is presented in recent paper [ 25 ]. Briefly, it was revealed that acid hydrolysis during incubation at pH 2.7 and 57 °C leads to the wild-type carbonic anhydrase cleavage into fragments of about 10 kDa and production of free and associated peptides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations